(untitled) (Theatrum historiae, 2024)
In this article different rebellions against the policy of Cardinal Richelieu in the 1630s in France are presented. Each of them has been analysed in terms of its causes and participants. In addition, attention was paid to their connection with the Thirty Years’ War. The main focus was placed on Gaston d’Orléans’ revolt, the Cascaveoux Revolt, and the Revolt of the va-nu-pieds. The rebellions are presented as stages of the development of absolutism.